2018
DOI: 10.1172/jci124944
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transplantation in humans: “magical” cure or cause for concern?

Abstract: Mitochondrial transplantation is a therapeutic approach developed by McCully and colleagues that entails the injection of healthy mitochondria harvested from unaffected tissue into an ischemic organ of the same subject (1). It has recently been applied to human pediatric patients with myocardial ischemia (2), receiving widespread media attention accompanied by sensationalistic claims on its mechanism of action, e.g.: (a) after injection into the heart, "mitochondria moved like magnets to the proper places in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 21 publications
0
46
0
1
Order By: Relevance
“…Here, our mitochondrial transfer method improved respiration in metabolically impaired cells containing endogenous, mutant mtDNA. Other studies performed mitochondrial transplantation into ρ+ cells in vitro 29,62 and in vivo [63][64][65][66][67][68] for therapeutic purposes, but only observed short term changes that do not indicate permanent retention of exogenous mtDNA. For example, one study restored ATP production in an A3243G MELAS cell line using Pep-1 mediated mitochondrial transfer 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, our mitochondrial transfer method improved respiration in metabolically impaired cells containing endogenous, mutant mtDNA. Other studies performed mitochondrial transplantation into ρ+ cells in vitro 29,62 and in vivo [63][64][65][66][67][68] for therapeutic purposes, but only observed short term changes that do not indicate permanent retention of exogenous mtDNA. For example, one study restored ATP production in an A3243G MELAS cell line using Pep-1 mediated mitochondrial transfer 62 .…”
Section: Discussionmentioning
confidence: 99%
“…These have led to pilot trials with a small number of paediatric patients with cardiac ischaemia who were undergoing ECMO (extracorporeal membrane oxygenation); a similar trial is currently recruiting (NCT02851758). Positive effects were reported with 4 of 5 patients showing improved ventricular function (Emani et al , ) but these studies have been questioned (Bertero et al , ). The group conducting these studies has previously suggested that at least part of the beneficial results could be caused by extracellular effects.…”
Section: Do Mitochondria Injected or Imported Into Cells Retain Activmentioning
confidence: 99%
“…Currently applied methodologies for mitochondrial transfer employs naked mitochondria and up to now, no delivery system has been reported. The use of naked mitochondria presents a limit in terms of delivery efficiency, due to the possible occurrence of mitochondrial damage and functional alteration during the isolation and transfer processes associated with no specific cellular target [28][29]. The possibility to encapsulate mitochondria within liposomes has been explored, but some difficulties have been found in organelle packaging [19].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these knowledge, McCully and colleagues employed mitochondrial transplantation as therapeutic approach to treat ischemia both in animal models and in pedriatic patients [18,36]. Mitochondrial transplantation is reported as a "magical" cure [28], since healthy organelles, harvested by unaffected tissue, after injection in the ischemic hearth move to the injured cells, rescue ATP energy production and improve the contractile function in 10 minutes [36]. However, this approach, as stated before, present some problems regarding mitochondrial survival during the transfer.…”
Section: Discussionmentioning
confidence: 99%